1997
DOI: 10.1126/science.278.5345.1934
|View full text |Cite
|
Sign up to set email alerts
|

Growth of SiO 2 at Room Temperature with the Use of Catalyzed Sequential Half-Reactions

Abstract: Films of silicon dioxide (SiO2) were deposited at room temperature by means of catalyzed binary reaction sequence chemistry. The binary reaction SiCl4 + 2H2O --> SiO2 + 4HCl was separated into SiCl4 and H2O half-reactions, and the half-reactions were then performed in an ABAB ellipsis sequence and catalyzed with pyridine. The pyridine catalyst lowered the deposition temperature from >600 to 300 kelvin and reduced the reactant flux required for complete reactions from approximately 10(9) to approximately 10(4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
242
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(259 citation statements)
references
References 18 publications
(5 reference statements)
12
242
0
1
Order By: Relevance
“…Previous studies have reported the use of Lewis bases such as NH 3 and pyridine as catalysts for low temperature growth of SiO 2 . 25,26 While these studies were done using gas phase reactants, it is possible that a similar mechanism is responsible for the growth of oxides on the SiGe surface in (NH 4 ) 2 S solutions which contain both NH þ 4 and NH 3 even though nitrogen species were not detected in the XPS (supplementary material, Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the use of Lewis bases such as NH 3 and pyridine as catalysts for low temperature growth of SiO 2 . 25,26 While these studies were done using gas phase reactants, it is possible that a similar mechanism is responsible for the growth of oxides on the SiGe surface in (NH 4 ) 2 S solutions which contain both NH þ 4 and NH 3 even though nitrogen species were not detected in the XPS (supplementary material, Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…The use of bases to catalyze the reaction SiCl 4 + 2 H 2 O!SiO 2 + 4 HCl, and reductive pulses in the preparation of nitride films represent some existing examples. [15,33] The third component may introduce a new element into the film, as is in the serendipitous case of WC x N y , where improved barrier properties and process integration were obtained.…”
Section: Angewandte Chemiementioning
confidence: 97%
“…ALD SiO 2 films may find application as protective or insulator coating, or can be used in nanolaminate structures with tailored optical and electronic properties. 10,11 The films can also be used in spacer defined double patterning processes for example for dynamic random access memory (DRAM) technology. 12 In addition, the ALD SiO 2 process may be useful for engineering the interface between Si and high-k materials.…”
mentioning
confidence: 99%
“…25 SiO 2 films grown with ALD have been reported to exhibit low carbon content, and a high electrical breakdown field. 10,22 Nevertheless, to improve properties such as the chemical etch rate or the interface defect density, annealing at a temperature of 1000…”
mentioning
confidence: 99%